Archeoseismology in Machu Picchu, paleoseismology and lacustrine records in Cuzco region as key interdisciplinary approaches for intraplate deformation characterization on the Andean Altiplano - Audin, Laurence (2018)
Trabajo presentado en el “6th Colloquium on historical earthquakes & paleoseismology studies : Their contribution to the knowledge of the long-term seismic activity and to seismic hazard assessment”, 24-26 October 2018, Han-sur-Lesse, Bélgica